-(2x-5)-(2x-5)+4=6(x-1)-(2x+7)+3

Simple and best practice solution for -(2x-5)-(2x-5)+4=6(x-1)-(2x+7)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x-5)-(2x-5)+4=6(x-1)-(2x+7)+3 equation:


Simplifying
-1(2x + -5) + -1(2x + -5) + 4 = 6(x + -1) + -1(2x + 7) + 3

Reorder the terms:
-1(-5 + 2x) + -1(2x + -5) + 4 = 6(x + -1) + -1(2x + 7) + 3
(-5 * -1 + 2x * -1) + -1(2x + -5) + 4 = 6(x + -1) + -1(2x + 7) + 3
(5 + -2x) + -1(2x + -5) + 4 = 6(x + -1) + -1(2x + 7) + 3

Reorder the terms:
5 + -2x + -1(-5 + 2x) + 4 = 6(x + -1) + -1(2x + 7) + 3
5 + -2x + (-5 * -1 + 2x * -1) + 4 = 6(x + -1) + -1(2x + 7) + 3
5 + -2x + (5 + -2x) + 4 = 6(x + -1) + -1(2x + 7) + 3

Reorder the terms:
5 + 5 + 4 + -2x + -2x = 6(x + -1) + -1(2x + 7) + 3

Combine like terms: 5 + 5 = 10
10 + 4 + -2x + -2x = 6(x + -1) + -1(2x + 7) + 3

Combine like terms: 10 + 4 = 14
14 + -2x + -2x = 6(x + -1) + -1(2x + 7) + 3

Combine like terms: -2x + -2x = -4x
14 + -4x = 6(x + -1) + -1(2x + 7) + 3

Reorder the terms:
14 + -4x = 6(-1 + x) + -1(2x + 7) + 3
14 + -4x = (-1 * 6 + x * 6) + -1(2x + 7) + 3
14 + -4x = (-6 + 6x) + -1(2x + 7) + 3

Reorder the terms:
14 + -4x = -6 + 6x + -1(7 + 2x) + 3
14 + -4x = -6 + 6x + (7 * -1 + 2x * -1) + 3
14 + -4x = -6 + 6x + (-7 + -2x) + 3

Reorder the terms:
14 + -4x = -6 + -7 + 3 + 6x + -2x

Combine like terms: -6 + -7 = -13
14 + -4x = -13 + 3 + 6x + -2x

Combine like terms: -13 + 3 = -10
14 + -4x = -10 + 6x + -2x

Combine like terms: 6x + -2x = 4x
14 + -4x = -10 + 4x

Solving
14 + -4x = -10 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
14 + -4x + -4x = -10 + 4x + -4x

Combine like terms: -4x + -4x = -8x
14 + -8x = -10 + 4x + -4x

Combine like terms: 4x + -4x = 0
14 + -8x = -10 + 0
14 + -8x = -10

Add '-14' to each side of the equation.
14 + -14 + -8x = -10 + -14

Combine like terms: 14 + -14 = 0
0 + -8x = -10 + -14
-8x = -10 + -14

Combine like terms: -10 + -14 = -24
-8x = -24

Divide each side by '-8'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x-1/x=4/3 | | 6(a+3)=9 | | 5x^2-37=43 | | 5x+7/3=2x+9 | | xy^3/y^5 | | x+15+x=x+45+x+40+x+25 | | (9n^6)^(1/2) | | 4=u+6 | | 40a^2+195+140=0 | | 8xy^3/6y^5 | | 4X-3=2-6X | | x^2-21x-216=0 | | (n+6)((n+6)-10)=200 | | -(7x-3)-(4x-5)+11=-3(x-1)-(11X+2)+3 | | 8x^204=28 | | (n^(-4/15))*(5n^(3/5)) | | 3/75=x/10 | | 6y+(3y+3)=16 | | n^-4/15*5n^3/5 | | -5m^2+245=0 | | ln(3x+1)+ln(x)=ln(2) | | 3(2y+3)=-3y-9 | | Y=-16x^2+384 | | 3n+5forn=4 | | 5x-1.2=9x-.8 | | 4+4-6x=35 | | 3(2x-1)=5x+2 | | 7/14= | | (-5/6)y(-3/4) | | -18=(9-x)/2 | | (-5/6)y | | -18=9-x/2 |

Equations solver categories